Combining Several Substitution Cipher Algorithms using Circular Queue Data Structure - Noor Ibraheem; Mokhtar Hasan (مجلة بغداد للعلوم, 2020)
With the revolutionized expansion of the Internet, worldwide information increases the application of communication technology, and the rapid growth of significant data volume boosts the requirement to accomplish secure, robust, and confident techniques using various effective algorithms. Lots of algorithms and techniques are available for data security.  This paper presents a cryptosystem that combines several Substitution Cipher Algorithms along with the Circular queue data structure. The two different substitution techniques are; Homophonic Substitution Cipher and Polyalphabetic Substitution Cipher in which they merged in a single circular queue with four different keys for each of them, which produces eight different outputs for every single incoming letter. The present work can be applied efficiently for personal information security and network communication security as well, and the time required for ciphering and deciphering a message is less than 0.1 sec.